SOCIO-CULTURAL DYNAMICS AND ETHNOLINGUISTIC VITALITY OF SEMBIRAN BALINESE - Desak Putu Eka Pratiwi; I Wayan Arka; Asako Shiohara (Linguistik Indonesia, 2020)
This paper reports our preliminary findings on the assessment of language vitality of Sembiran Balinese in the larger socio-cultural transformation of contemporary Bali.  Sembiran Balinese, also known as Bali Aga, is a conservative mountain dialect of Balinese spoken by around 5,000 speakers in the Sembiran village, 30 km east of Singaraja northern Bali. The language and its culture reflect Bali in antiquity (Ardika, et al. 1991; Ardika, et al. 1997), with the language quite distinct from Lowland Balinese (Bali Dataran), for example in terms of its pronominal system and the absence of speech level system (Astini 1996, Sedeng 2007, Arka & Sedeng 2018). The study is based on the data collected through questionnaires focusing on subjective views of ethno-linguistic vitality such as in-/out-group interactions and domains of language use in contemporary multilingual settings, supported by ethnographic data. The analysis makes use of the current development in the sociolinguistics of vitality, particularly the notions of ethnolinguistic vitality (Giles, et al 1977) and theories of language shift and endangerment (Grenoble & Whaley 2006, Fishman 1991). The findings reveal that Sembiran Balinese appears to have a relatively strong linguistic vitality even though the speech community itself is a minority group in Bali.